2004
DOI: 10.1074/jbc.m410128200
|View full text |Cite
|
Sign up to set email alerts
|

SMRT and N-CoR Corepressors Are Regulated by Distinct Kinase Signaling Pathways

Abstract: N-CoR and SMRT are corepressor paralogs that partner with and mediate transcriptional repression by a wide variety of metazoan transcription factors, including nuclear hormone receptors. Although encoded by distinct genetic loci, N-CoR and SMRT share substantial sequence interrelatedness, form analogous assemblies with histone deacetylases and auxiliary factors, can interact with overlapping sets of transcription factor partners, and exert overlapping functions in cells. SMRT is subject to negative regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 78 publications
4
70
0
4
Order By: Relevance
“…Notably, GPS2 is not only stably associated with SMRT complex, but has been shown to associate with N-CoR (23). There is evidence indicating that SMRT and N-CoR possess distinct functions in ER␣-mediated transcription (43)(44)(45)(46), and knockdown of SMRT or N-CoR alone relieves repression of ER␣ target genes (42). These observations suggest that SMRT/GPS2 and N-CoR/ GPS2 complexes may function independently.…”
Section: Discussionmentioning
confidence: 82%
“…Notably, GPS2 is not only stably associated with SMRT complex, but has been shown to associate with N-CoR (23). There is evidence indicating that SMRT and N-CoR possess distinct functions in ER␣-mediated transcription (43)(44)(45)(46), and knockdown of SMRT or N-CoR alone relieves repression of ER␣ target genes (42). These observations suggest that SMRT/GPS2 and N-CoR/ GPS2 complexes may function independently.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, MEKK1 and PI3K specifically regulate SMRT and N-CoR cytoplasmic export, respectively indicating the existence of other nonconserved domains. 13,15 Other post-transcriptional modifications may also regulate functional N-CoR and SMRT specificity, since it has recently been shown that N-CoR is sumoylated. 23 N-CoR and SMRT exert their function by recruiting repression elements to specific promoters and several transcription factors have been shown to interact with NCoRs such as Nuclear Receptors, RBPjk, p65, MyoD.…”
Section: Discussionmentioning
confidence: 99%
“…Specific protein kinases such as PI3K, CaMK-IV, ERK and IKKa have been reported to phosphorylate N-CoR and SMRT in different situations. [11][12][13][14][15] Moreover, phosphorylation of SMRT by IKKa results in increased affinity of the corepressor for the 14-3-3 adaptor proteins, thus inducing its cytoplasmic export. The 14-3-3 family is generally regulating subcellular localization of multiple proteins including cdc25, 16 FKHRL1, 17 HDACs 18 or NFkB.…”
Section: Introductionmentioning
confidence: 99%
“…The domain of the corepressors used in our assays is the domain that has been implicated in the repression of transcription via interaction with the POZ domains, PLZF or Bcl-6. This is a different domain from those (C-terminal) investigated by Privalsky and co-workers (42,43).…”
Section: Waf/cip1mentioning
confidence: 99%
“…Previously, the ability of SMRT to associate with a variety of transcription factors such as nuclear hormone receptors, PLZF, and Bcl-6, and thereby to mediate repression, was shown to be strongly repressed by the phosphorylation of SMRT by MEKK1 or MEK-1 of the MAP kinase pathway (42,43). More recently, it was demonstrated that the protein-protein interactions between the C-terminal nuclear receptor interaction domains of SMRT (S1, S2 domains; amino acids 1733-2471) or NCoR (N1-3 domains; amino acids 1946 -2435) and TR␣ or RAR␣ are differentially regulated by MEKK1, depending on the repressors (43). The domain of the corepressors used in our assays is the domain that has been implicated in the repression of transcription via interaction with the POZ domains, PLZF or Bcl-6.…”
Section: Waf/cip1mentioning
confidence: 99%